Surgical Outcome of Open Lumbar Microdiscectomy in Lumbar Disc Herniation Patients - Thapa, Bishnu Babu; Baskota, Narendra; Shah, Rajesh Pratap (Nepal Orthopaedic Association Journal, 2019)
INTRODUCTION: Lumbar disc herniation is common medical problem. PIVD presented with intractable pain or severe neurological symptoms related to nerve root compression. The most common herniation level is L4-L5, 95% rupture occurs at this levels. Almost 90% patients are relieved symptomatically with conservative treatment within 3 months period. There are various surgical methods if conservative treatment fails. The operative techniques are Open discectomy, microscopic discectomy, Standard microdiscectomy, endoscopic discectomy. The most commonly performed surgical procedure is standard microdiscectomy.METHODOLOGY: This is retrospective study of open lumbar microdiscectomy done at Shree Birendra Hospital from 2013 to 2018.The inclusion criteria are age